Analisis Diameter Mata Bor Terhadap Waktu Permesinan Dengan Variasi Putaran Spindel Pada Mesin Bor Vertikal LC-25A Terhadap Material Aluminium 5356 - Gegatama, Muhammad Henwa; Utama, Firman Yasa; Wulandari, Diah; Abdi, Ferly Isnomo (Jurnal Rekayasa Mesin, 2023)
The machining process in the era of Industry 4.0 is rapidly advancing over time, especially in production activities that require good quality and efficient time management. The completion of construction work, particularly in drilling machines, becomes a fundamental machining process that will influence subsequent machining processes. The diameter of the drill bit, spindle rotation speed, and workpiece material are among the aspects that can affect the machining time. One of the drilling machines at Mandiri Raya Teknik workshop is the First LC-25A Vertical Drilling Machine, which has not been in use for a long time. Therefore, there is a need for reference regarding the performance of this drilling machine. The aim of this research is to determine the influence of drill bit diameter and spindle speed on machining time. The research method used is experimental research, and the data analysis used is descriptive analysis. The drilling machine used is the First LC-25A type, with one HSS drill bit for each diameter: 5mm, 7.5mm, and 10mm. The test material used is Aluminum 5356, and the spindle speeds used are 1372.6 rpm, 1050.5 rpm, and 518.5 rpm. The results of this research show that the fastest average time was obtained for each drill bit diameter of 5mm, 7.5mm, and 10mm at a spindle speed of 1372.6 rpm, with average times of 25 seconds, 45 seconds, and 58.3 seconds, respectively.